BTX-A inhibited trigeminal neuralgia by blocking the NLRP3 pathway in rats - Se-Kyung Park; Jo-Young Son; Yu-Mi Kim; Jin-Sook Ju; Dong-Kuk Ahn (Brain Research Bulletin)
Few studies have examined the mechanisms underlying the development of trigeminal neuralgia involving the nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain-containing protein 3 (NLRP3). The purpose of this experiment was to investigate the role of NLRP3 in the antinociceptive effects of botulinum toxin type A (BTX-A) in trigeminal neuralgia. We used a trigeminal neuralgia animal model induced by injecting 1-acyl-2-lyso-sn-glycero-3-phosphate (LPA) into the trigeminal nerve root of rats. Rats treated with LPA showed a significant increase in the expression of NLRP3 in the trigeminal ganglion 9 days after LPA injection. Furthermore, the levels of interleukin (IL)-1β, IL-18, and tumor necrosis factor (TNF)-α increased on postoperative day 9. Subcutaneous administration of BTX-A (3 U/kg) in the vibrissa pad resulted in a significant attenuation of mechanical allodynia, and the antiallodynic effects lasted for 7 days. The upregulated NLRP3 expression in the trigeminal ganglion was suppressed 2 days after the injection of BTX-A. Moreover, the BTX-A injection significantly reduced the concentrations of IL-1β, IL-18, and TNF-α in the trigeminal ganglion. Intraganglionic injection of an NLRP3 inhibitor blocked mechanical allodynia and attenuated the upregulated cytokine concentrations in the LPA-treated rats. These results indicate that BTX-A induces its antinociceptive effects in the LPA-induced trigeminal neuralgia animal model by attenuating the NLRP3-cytokine pathway in the trigeminal ganglion.